Trends in Inuit health services utilisation in Manitoba: findings from the Qanuinngitsiarutiksait study. Issue 1 (31st December 2022) - Clark, Wayne; Lavoie, Josée G.; Mcdonnell, Leah; Nickel, Nathan; Anawak, Jack; Brown, Levinia; Clark, Grace; Evaluardjuk-Palmer, Maata; Ford, Frederick; Dutton, Rachel; Wong, Sabrina; Sanguins, Julianne; et al.
ABSTRACT: There is a notable lack of research related to trends in Inuit accessing health services throughout the land known as Canada. Given Nunavut's reliance on specialised services provided in the Northwest Territories, Alberta, Manitoba, and Ontario, this gap is particularly problematic, making it more difficult for Nunangat to proactively plan new programs for emerging needs, and for provinces to respond to those needs. The Qanuinngitsiarutiksait study aimed to address this gap by developing detailed profiles of Inuit accessing health services in Manitoba. We used administrative data routinely collected by Manitoba agencies, to support the development of Inuit-centric services. It was conducted in partnership with the Manitoba Inuit Association, and Inuit Elders from Nunavut Canada and Manitoba. We focused on two interrelated cohorts: Kivallirmiut (Inuit from the Kivalliq region of Nunavut) who come to Winnipeg to access specialised services; and Manitobamiut (Inuit already living in Manitoba). Findings show that health services are primarily accessed in Winnipeg. Half of health services accessed by Kivallirmiut are for in-patient care at facilities with the Winnipeg Regional Health Authority. The other half are for advanced out-patient care including specialist consults. For Kivallirmiut, hospitalisation for pregnancy and birth are the most prevalent reasons for hospitalisation, followed by diseases of the respiratory system. Noteworthy, rates of hospitalisation for conditions treatable in primary healthcare for Kivallirmiut are considerably lower than those for Manitobans living in the northern part of the province (where comparable constraints exist). For Inuit adults, rates of hospitalisation for these conditions are comparable to those of Manitobans living in small communities. Inuit living in Manitoba are most often hospitalised for mental health reasons, although other reasons are nearly as prevalent. Our results support the need for more Inuit-centric health programming in Winnipeg.